Uji Antagonis Trichoderma sp.T4 Terhadap Jamur yang Diisolasi dari Daun Bergejala Bercak Pada Bibit Kelapa Sawit (Elaeis Guineensis Jacq.) - Mukarlina, Tia Nirmala Hidayat Siti Khotimah, (Jurnal Protobiont, 2015)
The spot disease on leaves is a common disease that attacks the oil palm seedlings that is caused by several types of fungi. One of the alternatives to control this plant disease can be done with a biological control using biological agents such as the antagonistic fungus, i.e. Trichoderma sp. The research was conducted from January 2015 to April 2015 inLaboratory of Microbiology,Faculty of Mathematics and Natural Sciences, Tanjungpura University. The research aimed to find out the ability of Trichoderma sp. to control the fungi isolated from the leaves with spot disease symptoms on the oil palm seedlings. The isolation of the fungi of the leaves with spot disease symptoms was done through the direct isolation technique (direct planting) then the isolation of Trichoderma sp. T4 was conducted using the dilution method. The research obtained three types of fungi i.e.Curvularia sp. T1, Rhizoctonia sp. T2, and Fusarium sp. T3. The conclusion drawn from this research was that the Trichoderma sp. T4fungus was capable of slowing down the growth of the fungi isolated from the leaves with spot disease symptoms on the oil palm seedlings i.e.Curvularia sp. T1, Rhizoctonia sp. T2, and Fusarium sp. T3 by 34.01%, 30.42% and 41.69%, respectively.